2018
DOI: 10.1038/s41540-018-0058-z
|View full text |Cite
|
Sign up to set email alerts
|

Model-based identification of TNFα-induced IKKβ-mediated and IκBα-mediated regulation of NFκB signal transduction as a tool to quantify the impact of drug-induced liver injury compounds

Abstract: Drug-induced liver injury (DILI) has become a major problem for patients and for clinicians, academics and the pharmaceutical industry. To date, existing hepatotoxicity test systems are only poorly predictive and the underlying mechanisms are still unclear. One of the factors known to amplify hepatotoxicity is the tumor necrosis factor alpha (TNFα), especially due to its synergy with commonly used drugs such as diclofenac. However, the exact mechanism of how diclofenac in combination with TNFα induces liver in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…By integrating transcriptome analysis, machine learning, structural analysis, and live cell imaging, the authors showed that the maturation of multiprotein complexes required for IKK activation can be inhibited, thus effectively inhibiting NF-κB signaling. Oppelt et al [ 185 ] used a mathematical model to identify factors — IKK and free cytoplasmic IκBα—that contribute to increased hepatotoxicity caused by the combination of TNF-α and the anti-inflammatory drug diclofenac. They not only proposed a new mathematical model of NF-ĸB but also used it to assess the safety of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…By integrating transcriptome analysis, machine learning, structural analysis, and live cell imaging, the authors showed that the maturation of multiprotein complexes required for IKK activation can be inhibited, thus effectively inhibiting NF-κB signaling. Oppelt et al [ 185 ] used a mathematical model to identify factors — IKK and free cytoplasmic IκBα—that contribute to increased hepatotoxicity caused by the combination of TNF-α and the anti-inflammatory drug diclofenac. They not only proposed a new mathematical model of NF-ĸB but also used it to assess the safety of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the NF-κB pathway by computational approaches has so far been mostly addressed by mathematical, dynamic pathway modeling using ordinary differential equations (ODEs) of the signaling pathway 30 , but the structural biology has not been fully exploited yet. Computational studies have proven to play an integral role in linking theoretical biophysics to the fields of experimental cell biology, clinical pharmacology and medicine.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The search for potent and safe NF-κB inhibitors is of paramount importance as it may represent a novel therapeutic strategy for many diseases including inflammatory diseases and viral infections. While the full structural details of NF-κB have not been characterized yet, computational studies have thus far used mathematical modeling and simulation tool to investigate NF-κB and its signaling pathways 34 . Predictions made by various in silico studies which were successfully complemented by wet lab studies have advanced our understanding of NF-κB signaling pathways 35 .…”
Section: Introductionmentioning
confidence: 99%